(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research seeks to identify the theoretical framework of the trust account and the role of the external auditor in verifying the accuracy of its registration, registration, control and liquidation. A proposed audit program has been prepared for approval by the external auditor in auditing the trust account in accordance with international auditing standards, which is what the research aims to achieve The research found that, Not to rely entirely on INTOSAI standards and international auditing standards when preparing the financial statements audit program for the government spending unit approved for all audit procedures related to the trust account as only (8) procedures were included in the approved program (Appendix No. (1)), as these procedures are considered insufficient to audit the trusts account because it includes accounts. There are many sub-subjects, and the research recommends adopting the proposed audit program to audit the trusts account.